Partially identified treatment effects under imperfect compliance: the case of domestic violence - Zahra Siddique (Institute for the Study of Labor (IZA), 2009)
During the 1980s a set of randomized experiments were carried out to determine the usefulness of a mandatory arrest policy for domestic assault offenders. The first of these was the Minneapolis Domestic Violence experiment (MDVE), which was carried out in 1981. This paper re-examines the data from the MDVE and uses the recent literature on partial identification to determine the implications for a mandatory arrest policy for domestic assault offenders today. I find support for a mandatory arrest policy for domestic assault offenders, even under a set of minimal assumptions on offender and police behavior.
Keywords: C9; C14; K42; 330; Partial identification; experiments; illegal behavior; policing; Kriminalpolitik; Gewalt; Strafvollzug; Wirkungsanalyse; Test; USA